Problematika Pengelolaan Tanah Wakaf: Konsep Klasik dan Keterbatasan Inovasi Pemanfaatannya di Indonesia - Agus Triyanta; Mukmin Zakie (Jurnal Hukum IUS QUIA IUSTUM, 2014)
This study raises the issue on; first, how is the classic concept of waqaf land and the use of waqaf land in Islamic law or muamalah jurisprudence? Secondly, how is the utilization of donated land and its contribution to the welfare of the people in Indonesia? This is a normative study combined with field research. The data were collected through literatures, documentation studies, observations, and guided interviews. The study concluded; first, institution or charitable institutions have a role in the history and civilization of Muslims. Various institutions have functioned to serve as a dissemination of science and culture, and provide spaces for scholars, jurists and humanists to develop their knowledge and skills. Secondly, the use of donated land in Indonesia is dominated for the purposes of a place of worship, school infrastructure, other social endowments, land burial and educational boarding schools.